Salivary Creatinine Estimation as an Alternative to Serum Creatinine in Chronic Kidney Disease Patients. (10th April 2014) - Venkatapathy, Ramesh; Govindarajan, Vasupradha; Oza, Nirima; Parameswaran, Sreejith; Pennagaram Dhanasekaran, Balamurali; Prashad, Karthikshree V.
Abstract : Context . Sampling blood for serum analysis is an invasive procedure. A noninvasive alternative would be beneficial to patients and health care professionals. Aim . To correlate serum and salivary creatinine levels and evaluate the role of saliva as a noninvasive alternative to serum for creatinine estimation in chronic kidney disease patients. Study Design . Case-control study. Methods . Blood and saliva samples were collected from 37 healthy individuals and 105 chronic kidney disease patients. Serum and salivary creatinine levels were estimated using automatic analyser. Statistical Analysis . The serum and salivary creatinine levels between controls and cases were compared usingt -test. Correlation between serum and salivary creatinine was obtained in controls and cases using Pearson correlation coefficient. Receiver operating characteristic analysis was done to assess the diagnostic performance of salivary creatinine. Cut-off values were established for salivary creatinine. Results . Serum and salivary creatinine levels were significantly higher in CKD patients than controls. The correlation was negative in controls and positive in cases. Area under the curve for salivary creatinine was found to be 0.967. A cut-off value of 0.2 mg/dL gave a sensitivity of 97.1% and specificity of 86.5%. Conclusion . Saliva can be used as a noninvasive alternative to serum for creatinine estimation.